2017
DOI: 10.1017/neu.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive N-acetylcysteine in depression: exploration of interleukin-6, C-reactive protein and brain-derived neurotrophic factor

Abstract: Overall, this suggests that our results failed to support the hypothesis that IL6, CRP and BDNF are directly involved in the therapeutic mechanism of NAC in depression. IL6 may be a useful marker for future exploration of treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
(56 reference statements)
1
18
0
Order By: Relevance
“…Table 1C additionally shows that there are also two out of three studies (57, 58) that showed that in the case of add-on n -acetyl cysteine, it was of no use to stratify the patients in low- or high-grade inflammation prior to therapy. Two of the studies of add-on n -acetyl cysteine (one showing and one not showing an effect of prior determination of the inflammatory state) involved both unipolar and bipolar depressed patients.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1C additionally shows that there are also two out of three studies (57, 58) that showed that in the case of add-on n -acetyl cysteine, it was of no use to stratify the patients in low- or high-grade inflammation prior to therapy. Two of the studies of add-on n -acetyl cysteine (one showing and one not showing an effect of prior determination of the inflammatory state) involved both unipolar and bipolar depressed patients.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-two studies were able to provide data of response to exclusively pharmacological treatment and two studies provided the cytokine values by combining both pharmacological and non-pharmacological treatments 24,31 . Three studies pre-selected treatment-resistant patients to study the effect of augmentation treatments [32][33][34] .…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A newer trial which explores effects of adjunctive N-acetylcysteine treatment on inflammatory and neurogenesis markers in the unipolar depression provided additional supporting evidence. [ 48 ] In this double-blind, placebo-controlled trials with 252 participants, N-acetylcysteine treatment of 2000 mg/day significantly improved depressive symptoms over the 16 weeks trial period compared to placebo. [ 48 ] However, the study failed to find any relevant inflammatory and neurogenesis marker that directly involved in the therapeutic mechanism of N-acetylcysteine in depression.…”
Section: Clinical Evidencementioning
confidence: 99%
“…[ 48 ] In this double-blind, placebo-controlled trials with 252 participants, N-acetylcysteine treatment of 2000 mg/day significantly improved depressive symptoms over the 16 weeks trial period compared to placebo. [ 48 ] However, the study failed to find any relevant inflammatory and neurogenesis marker that directly involved in the therapeutic mechanism of N-acetylcysteine in depression. [ 48 ] An upcoming 16-week trial which investigates N-acetylcysteine and a combination of other mitochondrial agents compared with placebo was described in the literature.…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation